2006
DOI: 10.1065/espr2006.06.311
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxic Effect of Photocatalytic Active Nanoparticles (TiO2) on Algae and Daphnids (8 pp)

Abstract: First results are presented which indicate that the topic 'ecotoxicity and environmental effects of nanoparticles' should not be neglected. In testing photocatalytic nanoparticles, there are still many topics that need clarification or improvement, such as the cause for an observed toxicity, the improvement of the test design, the elaboration of a test battery and an assessment strategy. On the basis of optimized test systems, it will be possible to test nanoparticles systematically. If a potential risk by spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
226
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(238 citation statements)
references
References 15 publications
8
226
2
2
Order By: Relevance
“…One of the earlier studies using the green algae Desmodesmus subspicatus found no statistically significant differences associated with irradiation before TiO 2 NP (25 and 100 nm) exposures, nor an effect of shading [51]. Similarly, Van Hoecke et al [52] found no effects of shading on Pseudokirchneriella subcapitata during experiments with CeO 2 NPs.…”
Section: Critical Variations In Protocols For the Microalgae Testmentioning
confidence: 90%
“…One of the earlier studies using the green algae Desmodesmus subspicatus found no statistically significant differences associated with irradiation before TiO 2 NP (25 and 100 nm) exposures, nor an effect of shading [51]. Similarly, Van Hoecke et al [52] found no effects of shading on Pseudokirchneriella subcapitata during experiments with CeO 2 NPs.…”
Section: Critical Variations In Protocols For the Microalgae Testmentioning
confidence: 90%
“…Their results showed that the increasing concentration of Cadmium and Zinc is related to NPs adsorption in Daphnia magna experiments. Although previous studies have examined the potential effects of nano-TiO 2 , those that specifically studied the ecotoxicity of nano-TiO 2 are limited on acute and chronic experiments (Hund-Rinke and Simon, 2006;Federici et al, 2007;Heinlaan et al, 2008;Wiench et al, 2009). Therefore, the present study investigated the carrier effect of nano-TiO 2 in the aquatic environment and described the ecotoxicological effects of concomitant exposure to Pb and nano-TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the European Union Directive on classification, packaging and labeling of dangerous substances (Council Directive 67/548/EEC), a toxicity in the range of 10-100 mg.L -1 combined with a lack of biodegradability has to be classified as 'harmful to aquatic organisms and may cause long-term adverse effects in the aquatic environment' [28]. Our results demonstrate that even low doses such as 1 mg.L -1 of a TiO 2 -Np sunscreen formulation is enough to induce significant cell sedimentation.…”
Section: Resultsmentioning
confidence: 57%
“…Hund-Rinke et al [28] explained that part of the algal inhibition by TiO 2 -Np is probably not caused by the reduced light intensity, but is due to the toxicity of the particles. The sensitivity of other algae to TiO 2 -Np has been previously described [29]; for example, P. subcapitata is more sensitive to nanosized TiO 2 than C. reinhardtii, followed by D. subspicatus.…”
Section: Nanoecotoxicological Effects Of a Sunscreen Formulation Basementioning
confidence: 99%